Dental anxiety and fear - Oba, Vivian C.; ADAMU, VE; Eneojo, Ndidiamaka Ijeoma (Orapuh Journal, 2020)
Anxiety or fear is a reaction to a known or perceived threat or danger. Dental anxiety or fear is a reaction to a known or perceived threat or danger in the dental facility or environment. Some genetic, behavioural, and cognitive factors contribute to the aetiology of dental anxiety and fear. The prevalence of dental anxiety and fear has not notably decreased over time, despite efforts that have been made to reduce or treat it. Dental anxiety and fear may have long-lasting complications. There are different instruments for the assessment of dental anxiety or fear - both in children and adults. The method used for the assessment of dental anxiety or fear involves the use of the Modified Dental Anxiety Scale (MDAS). Dental anxiety and fear are real. But taking steps to reduce them may improve dental attendance, and the quality of time spent at a dental facility during visits and enhance treatment outcomes.